Temporal Trends in the Epidemiology of HIV in Turkey - Erdinc, F. S.; Dokuzoguz, B.; Unal, S.; Komur, S.; Inkaya, A. C.; Inan, D.; Gokengin, D. (Bentham Science Publ Ltd, 2020)
Objective: The aim of this study was to analyze the temporal trends of HIV epidemiology in Turkey from 2011 to 2016. Methods: Thirty-four teams from 28 centers at 17 different cities participated in this retrospective study. Participating centers were asked to complete a structured form containing questions about epidemiologic, demographic and clinical characteristics of patients presented with new HIV diagnosis between 2011 and 2016. Demographic data from all centers (complete or partial) were included in the analyses. For the cascade of care analysis, 15 centers that provided full data from 2011 to 2016 were included. Overall and annual distributions of the data were calculated as percentages and the Chi square test was used to determine temporal changes. Results: A total of 2,953 patients between 2011 and 2016 were included. Overall male to female ratio was 5:1 with a significant increase in the number of male cases from 2011 to 2016 (p<0.001). The highest prevalence was among those aged 25-34 years followed by the 35-44 age bracket. The most common reason for HIV testing was illness (35%). While the frequency of sex among men who have sex with men increased from 16% to 30.6% (p<0.001) over the study period, heterosexual intercourse (53%) was found to be the most common transmission route. Overall, 29% of the cases presented with a CD4 count of >500 cells/mm(3) while 46.7% presented with a CD4 T cell count of <350 cells/mm(3). Among newly diagnosed cases, 79% were retained in care, and all such cases initiated ART with 73% achieving viral suppression after six months of antiretroviral therapy. Conclusion: The epidemiologic profile of HIV infected individuals is changing rapidly in Turkey with an increasing trend in the number of newly diagnosed people disclosing themselves as MSM. New diagnoses were mostly at a young age. The late diagnosis was found to be a challenging issue. Despite the unavailability of data for the first 90, Turkey is close to the last two steps of 90-90-90 targets.
Keywords: HIV; AIDS; Epidemiology; Co-infection; diagnosis; fatality; HBV; HCV